BUDIDAYA UDANG VANNAMEI (Litopenaeus vannamei) DENGAN SISTEM INTENSIF PADAT PENEBARAN 200 dan 300 EKOR/M2: INDONESIA - Rizal, Rizal Aji Prasetya; Mahmuda Noor, Nuning; Puji Hartono, Dwi (Jurnal Perikanan Terapan, 2022)
Vannamei Shrimp (Litopenaeus vannamei) is a commodity that is widely cultivated. This is because the shrimp has promising prospects and profits. This activity aims to determine the growth and survival of vannamei shrimp (Litopenaeus vannamei) with a stock density of 200 and 300 individuals/m2. During maintenance the observations made included growth, survival rate, feed conversion ratio and water quality. Vannamei shrimp rearing was carried out for 90 days with a stocking density of 200 individuals/m2 and 300 individuals/m2. The growth results of vannamei shrimp culture with a stocking density of 200 and 300 individuals/m2 showed different results in each pond during 90 days of maintenance. The growth of vannamei shrimp every week has increased in growth. Survival in vannamei shrimp farming ranges from 87.74-87.99%. In pond 1, the survival rate was 87.74%, then in pool 2, the survival rate was 87.99%.